The Open Incubator Model - Bijaoui, Ilan. author. aut Link
X, 140 p.
Keywords: The Open Incubator Model analyzes the different support policies needed in big cities, rural areas and country borders for entrepreneurs in developed and developing countries to generate cooperation and improve the business models of local SMEs.